PATIENTS SAFETY CULTURE DEVELOPMENT IN JAMBI PUBLIC HOSPITAL - Anastasia Yekti Heningnurani; Dumilah Ayuningtyas (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Patient safety is a serious issue in a healthcare organization. Building a patient safety culture is the first step in the improvement of safety. As patient safety culture is an inherent component of organizational culture; therefore, a study of organizational culture is required to develop it. This study aims to analyze the patient safety culture and identify the profile of the organizational culture in the hospital to find strategies to improve the patient safety culture. Methods: This study was used the quantitative study using a cross-sectional research method, followed by a qualitative method to get descriptive information. This research conducted in Jambi Public Hospital, Indonesia with 128 respondents. Data were obtained from a survey by the HSOPSC (Hospital Survey on Patient Safety Culture) questionnaire and OCAI (Organizational Culture Assessment Instrument. Focus Group Discussion was conducted to identify obstacles and expectations in the implementation of patient safety culture. Results: The highest positive perceptions are organizational learning and continuous improvement (90.6%) and teamwork within units (78.91%). While